Kesiapan Siswa dalam Menghadapi Pembelajaran Digital: Analisis Bibliometrik - Thahir, Muthahharah; Amalia, Kaniati; Thahir, Wahyuni; Widiawati, Widiawati; Asri, Kholifatul Husna; Nurlatifah, Siti (Universitas Mathla'ul Anwar Banten, 2023)
This study aims to map the results of publications on the topic of student readiness and digital learning. The method used is bibliometric analysis. The data used in this research comes from CrossRef. The data search is carried out through the Publish or Perish application. The search results yielded a total of 599 articles in English. The keywords used to search for articles are